INNOVATION MACARONI PASTA OF BASED LUMI-LUMI FISH-ENDEMIC AND EFFECT OF BOILING METHOD PROCESS ON NUTRITIONAL CONTENT - Safrida; Rahma, Cukri; Rinawati; Harahap, Laila Apriani Hasanah; Budijanto, Slamet; Kurniati , Yeni; Lubis, Friyuanita (Media Teknologi Hasil Perikanan, 2024)
Meulaboh is located in the western part of Sumatra Island, West Aceh Regency, Aceh Province. Coastal areas in the Meulaboh have an endemic type of fish, lumi-lumi (Harpodon nehereus), which is known to contain various micronutrients and proteins. The study aimed to identify the best macaroni formulation based on good sensory acceptability, micronutrient content, nutritional value, and protein. The treatment used was a different concentration of Lumi-lumi fish meat on macaroni dough, namely: P1(15%), P2(20%), and P3(25%). The best macaroni formulation was determined using scoring analysis based on sensory parameters. The participants consisted of 30 untrained panelists.  Then the best products were tested for changes in nutritional content, soluble protein, and minerals, before and after boiling for 15 minutes using a paired t-test with alpha 5%. The study showed that the selected formulation was P1(15%), with the highest total score of 18. The results show the boiling process significantly increases the moisture, ash, and fat content, namely 71.70%, 1.67%, and 4.73%, respectively on the P1 (15%) product. Meanwhile, it reduces the crude protein, fiber, carbohydrate, and soluble protein content by 8.41%, 1.63%, 11.86%, and 16.8 ug/L. Then, it also reduces a number of minerals, namely calcium, magnesium, copper, zinc, and selenium. In conclusion, the macaroni formulation P1 is better based on consumer acceptance with color value 4.71(slightly-liked), aroma 4.28(indifferent), taste 4.21(indifferent), hardness 4.71(slightly-liked), elasticity 4.82(slightly-liked), and overall acceptance 4.51(slightly-liked). Kata kunci:  Harpodon nehereus, Lumi-lumi, Macaroni, Nutrition, Sensory   Meulaboh terletak di sebelah Barat Laut Pulau Sumatra, Kabupaten Aceh Barat, Provinsi Aceh. Perairan di wilayah meulaboh memiliki jenis ikan endemik lumi-lumi (Harpodon nehereus) yang diketahui mengandung berbagai mikronutrien dan protein. Tujuan penelitian yaitu mengidentifikasi formulasi makaroni terbaik berdasarkan daya terima sensori yang baik, dengan kandungan mikronutrien, nilai gizi, dan protein. Perlakuan penelitian yaitu konsentrasi daging ikan Lumi-lumi yang berbeda pada adonan makaroni meliputi: P1(15%), P2(20%), dan P3(25%). Formulasi makaroni terbaik ditentukan dengan analisis skoring berdasarkan parameter sensori. Peserta terdiri dari 30 panelis tidak terlatih. Kemudian produk terbaik diuji perubahan kandungan gizi, protein terlarut, dan mineral, sebelum dan setelah perebusan selama 15 menit menggunakan uji t berpasangan alpha 5%. Hasil penelitian menunjukkan formulasi terbaik adalah P1(15%) dengan total skoring tertinggi yaitu 18 skor. Kemudian proses perebusan meningkatkan kadar air, abu, dan lemak secara signifikan yaitu masing-masing sebesar 71,70%, 1,67%, dan 4,73% pada produk P1 (15%). Sementara proses perebusan menurunkan kandungan protein kasar, serat, karbohidrat, dan protein larut sebesar 8,41%, 1,63%, 11,86%, dan 16,8 ug/L. Kemudian, juga mengurangi sejumlah mineral yaitu kalsium, magnesium, tembaga, seng, dan selenium. Kesimpulannya formulasi makaroni P1 lebih baik berdasarkan penerimaan konsumen dengan nilai warna 4.71 (agak-suka), aroma 4.28 (normal), rasa 4.21 (normal), kekerasan 4.71 (agak-suka), kekenyalan 4.82 (agak-suka), dan penerimaan keseluruhan 4.51 (agak-suka). Kata kunci:  Harpodon nehereus, Lumi-lumi, Makaroni, Nutrisi, Sensori